(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The solvents used in chemistry are a fundamental element of the environmental performanceof processes in corporate and academic laboratories. Their influence on costs, health safety, and naturecannot be neglected. Quantitatively, solvents are the most abundant constituents of chemicaltransformations therefore, acting on solvents and replacing standard solvents with safer products canhave a great ecological impact. However, not all green solvents are suitable for the wide scope oforganic chemistry reactions. With this inspiration in our mind, in the present paper we developed asustainable catalytic system using water as catalyst towards the synthesis of substituted aromaticaminals. The present methodology is fast, easy and eco friendly thereby following the sustainableprinciples of green chemistry. In this paper we developed sustainable method for eco-friendly synthesisof diverse substituted aminals in the absence of catalystreagentsadditivesinert atmosphere undersolvent free conditions. The present protocol is beneficial because of proficient synthetic layout, widesubstrate scope with good to excellent yields, good E-factor of 0.20 and high reaction mass efficiency of83.